1998
DOI: 10.1046/j.1365-2915.1998.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the second‐ and third‐instar larvae of Dermatobia hominis by scanning electron microscopy

Abstract: Larvae of Dermatobia hominis 10-27 days old were collected from experimentally infected rats and their morphology was studied by scanning electron microscopy. The moult from the second to third instar occurs at 18 days, with emergence from the host at 30 days post-infection. The second-instar larvae bear on the pseudocephalon, antennae (coeloconic sensilla), and coeloconic and basicoconic sensilla on the maxillary sensory complex. The thoracic segments bear small backwardly-directed spines anteriorly and ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…6 Scanning electron microscopy of the first-and second-instar larvae of D hominis revealed small backwardly-directed spines on the thoracic segments, small and large backwardly-directed spines on the first four abdominal segments, and forwardly-directed spines on the seventh and eight abdominal segments. 128,129 de Filippis and Leite 128 reported small preoral spines on the first thoracic segment and flat, thorn-like spines on the second and third thoracic segments and the first four abdominal segments of the third instar larvae of D hominis. The spines of the third instar larvae were noted to have a similar arrangement to those of the second instar larvae except for a small number of forwardly-directed spines on the first to fourth abdominal segments.…”
Section: Occlusionmentioning
confidence: 97%
See 2 more Smart Citations
“…6 Scanning electron microscopy of the first-and second-instar larvae of D hominis revealed small backwardly-directed spines on the thoracic segments, small and large backwardly-directed spines on the first four abdominal segments, and forwardly-directed spines on the seventh and eight abdominal segments. 128,129 de Filippis and Leite 128 reported small preoral spines on the first thoracic segment and flat, thorn-like spines on the second and third thoracic segments and the first four abdominal segments of the third instar larvae of D hominis. The spines of the third instar larvae were noted to have a similar arrangement to those of the second instar larvae except for a small number of forwardly-directed spines on the first to fourth abdominal segments.…”
Section: Occlusionmentioning
confidence: 97%
“…Spines with double and triple points were also observed in the third instar larva. 129 Recently, Möhrenschlager et al 130 performed scanning electron microscopy on a third instar D hominis larva and noted small, forwardly-directed spines in several circular rows at the caudad end. Like de Filippis and Leite, 128 Möhrenschlager et al 130 also reported flat, thorn-like spines on the second and third thoracic segments and on the first four abdominal segments of the third instar larvae.…”
Section: Occlusionmentioning
confidence: 98%
See 1 more Smart Citation
“…Animal infection: Each animal from 10 groups of six male Swiss mice (20-25g) was submitted to skin infection with one newly hatched larva of D. hominis reared in our laboratory 9 . The mice were sacrificed and spleens obtained from groups 1-5 at 5, 10, 15, 20 and 25 days-postinfection (dpi), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Five groups with five male adult Wistar rats (190-220g) were infested with four newly hatched larvae of D. hominis and sacrificed at 5, 10, 15, 20 and 25 dpi to collect the larvae from the skin tissues 9 . Larvae at each infested date were washed three times with RPMI-1640 medium (Sigma) and conditioned in Falcon tubes with 2 mL of RPMI for incubation at 37 ºC in a 5% CO 2 …”
Section: Larval Secretory Product (Lsp)mentioning
confidence: 99%